The efficacy of nasal administration of esketamine in patients having moderate-to-severe pain after preoperative CT-guided needle localization: a randomized, double-blind, placebo-controlled trial - Xu, Jiangning; Jian, Jin; Zhang, Yunyun; Wu, Jingxiang; Qiu, Yuwei (Frontiers in Medicine, 2024)
Background Whether nasal administration of esketamine can provide effective analgesia is unclear in patients with acute pain after preoperative CT-guided needle localization. Methods In this double-blind, randomized, placebo-controlled trial, patients were assigned to receive either nasal administration of esketamine (0.3 mg/kg or 0.5 mg/kg) or saline (identical in appearance to esketamine) when they had visual analog scale (VAS) pain scores >3/10 during deep breathing after preoperative CT-guided needle localization. The primary outcome was the percentage of patients with satisfactory pain relief, which was defined as VAS pain scores ≤3/10 measured 15 min after intranasal of esketamine or saline. Secondary outcomes included VAS measured following esketamine or saline, the incidence and cumulative dose of rescue hydromorphone use, and related adverse events. Results A total of 90 patients were included in the final analysis. Following intranasal treatment, the percentage of patients with satisfactory pain relief was 16.7% (5/30) in the saline group, 56.7% (17/30) in the 0.3 mg/kg esketamine group, and 53.3% (16/30) in the 0.5 mg/kg esketamine group (p = 0.002). The median VAS during deep breathing was less after the intranasal administration of esketamine median (IQR), 3 (3, 5) in 0.3 mg/kg or 0.5 mg/kg esketamine compared to the saline group [5 (4, 6)], p = 0.009. The incidence of rescue hydromorphone use was detected less in the esketamine group compared to the saline group (43.3% in the 0.3 mg/kg esketamine group, 36.7% in the 0.5 mg/kg esketamine group, and 73.3% in the saline group, p = 0.010). The adverse events were similar among the three groups (p > 0.05). Conclusion Intranasal administration of esketamine is easier and more effective in alleviating acute pain in patients after preoperative CT-guided needle localization without significant adverse effects.